GPT- 4 as a virtual fitness coach: a case study assessing its effectiveness in providing weight loss and fitness guidance - Guanchong Li; Hansen Li; Yuqin Su; Yun Li; Sijia Jiang; Guodong Zhang (BMC Public Health)
Abstract Background As obesity presents a growing public health challenge, demand for personalized fitness solutions has increased. This study evaluates GPT-4's effectiveness as a virtual fitness coach for creating personalized plans. Method A 24-year-old Chinese female's data was used by GPT-4 and three professional coaches to develop 16-week fitness plans. Experts evaluated these plans on personalization, effectiveness, comprehensiveness, and safety. Statistical analyses were performed. Results GPT-4 excelled in personalization (M = 12.80, SD = 0.84) compared to coaches (M = 11.53, SD = 0.46), However, the difference wasn't big enough to be considered statistically significant (p > 0.05). In terms of effectiveness (GPT-4: M = 12.60, Coaches: M = 12.80), safety (GPT-4: M = 12.20, Coaches: M = 12.33), and comprehensiveness (GPT-4: M = 12.00, Coaches: M = 12.13), coaches slightly outperformed GPT-4, But again, these differences didn't reach statistical significance (p > 0.05). Conclusions GPT-4 shows promise as a virtual fitness coach but cannot fully replace human coaches due to technological limitations. Future research should explore enhancing AI models' applicability in sports and their collaboration with coaches for optimal personalized fitness solutions.